2019
DOI: 10.3855/jidc.11604
|View full text |Cite
|
Sign up to set email alerts
|

A glimpse of the bacteriome of Hyalomma dromedarii ticks infesting camels reveals human Helicobacter pylori pathogen

Abstract: Introduction: The tick Hyalomma dromedarii is predominant in camels of Saudi Arabia and harbor multiple pathogens causing disease in humans and animals. Knowing the bacterial community of ticks is crucial for surveillance of known and newly emerging pathogens. Yet, the bacteriome of H. dromedarii remain unexplored to date. Methodology: In a cross-sectional survey, we used V3-V4 region of 16S rRNA to characterize the bacteriome of 62 whole H. dromedarii tick samples collected from camels found in Hofuf ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
4
9
1
Order By: Relevance
“…Bacillus , Escherichia , Siccibacter and Acinetobacter were the other predominant genera at different locations in 2019 samples. The genus Francisella was confirmed previously in H. dromedarii ticks from Palestine 47 and Saudi Arabia 48 .…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Bacillus , Escherichia , Siccibacter and Acinetobacter were the other predominant genera at different locations in 2019 samples. The genus Francisella was confirmed previously in H. dromedarii ticks from Palestine 47 and Saudi Arabia 48 .…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, the genus level identifications presented in the current study are provided as preliminary baseline data, which may require further confirmation. Our results indicated that Acinetobacter and Corynebacterium were the two most abundant genera detected in the microbiota of H. dromedarii from all locations with high sequence ratios 47 and Saudi Arabia 48 . We found significant associations between Acinetobacter, Escherichia and Francisella and between these three genera and several other genera.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the DNA-pool 2, more than 66 genera were identified with a percentage of distribution ranging from 0.87% to 0.01%. These genera include among others: [36]. This approach facilitates the identification of more microorganisms as compared to the PCR-based techniques targeting specific known pathogens.…”
Section: Resultsmentioning
confidence: 99%